Non-knowledge risk and bank-company management : the role of intangibles in rating models - Vincenzo Formisano (2024)
In this book, Vincenzo Formisano proposes new guidelines aimed to set desirable IRSs in which the weight of intangible assets is appropriately and properly valued. He addresses practical rules for achieving a rating system capable of understanding and enhancing the intangible assets of a company and for the assessment of creditworthiness.